Taxi para 3 = A cab for 3 - Muñoz, Daniel 1966-; Gómez Rovira, Fernando 1973-; Trejo, Alejandro 1959- (Maverick Latino, 2003)
A black comedy telling the story of Ulises, a taxi driver who thinks that joining the gang that holds him up may just be the way out